Mycorrhizal Influence on Irrigation Efficiency: A Study of Maize under Drought Conditions - Gültekin, Rohat; GÖRGİŞEN, Ceren and ํYeter Tuğba and Sagun, Çağlar and Avağ, Kadri (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Drought stress is one of the biggest threats to agriculture in different parts of the world, especially in countries in the Mediterranean climate zone. One of the most natural solutions for agricultural sustainability is to use fungi that can establish symbiotic relationships with agricultural products. In this study, the effectiveness of different arbuscular mycorrhizal fungi that can help reduce drought stress in maize plants was tested. The findings revealed that arbuscular mycorrhiza fungi inoculation significantly improved both irrigation water use efficiency (IWUE) and plant biomass under drought stress compared to non-inoculated controls. Notably, Rhizophagus intraradices and Glomus iranicum showed the highest enhancements in IWUE and yield. For example, R. intraradices achieved an irrigation water use efficiency of 16.2 kg/m³ under low drought stress (70% of field capacity) and a yield of 26.9 t ha-1. Under moderate drought stress (50% of field capacity), this species maintained a high IWUE of 16.1 kg m-3 and a yield of 18.4 t ha-1. In severe drought conditions (30% of field capacity), R. intraradices still performed well with an IWUE of 13.5 kg m-3 and a yield of 10.9 t ha-1. Overall, AMF-treated plants exhibited 30-50% higher WUE compared to controls, with G. iranicum and R. intraradices being the most effective in enhancing drought tolerance and plant productivity. These results suggest that integrating AMF into maize cultivation can contribute to sustainable agricultural practices, particularly in regions facing water scarcity.